What Kind of Island in What Kind of Sea? - Fühmann, Franz (Lever Press, 2021)
The dignity of cognitively disabled people and the ethics of representing their lives are at the heart of an extraordinary yet little-known book first published in the former German Democratic Republic. Was für eine Insel in was für einem Meer, or What Kind of Island in What Kind of Sea (Rostock, Hinstorff, 1986) depicts residents of a church-run institution for people with cognitive disabilities in astonishing black-and-white photographs by Dietmar Riemann and in a probing, poignant essay by esteemed German writer Franz Fühmann. This important text, which moved from a medical model to a historical and cultural view of disability as an aspect of human identity and experience, is translated into English for the first time by Elizabeth Hamilton and includes reflections on the book and its impact. As fuller, global histories of disability are now being written, What Kind of Island in What Kind of Sea opens an essential window onto a formerly shuttered world, demonstrating the power of the arts to hone our capacity to perceive and appreciate human difference.